Immigration projects among young doctors in Tunisia: Prevalence, destinations and causes. (1st June 2022) - Ajmi, M.; Kahloul, M.; Kacem, I.; Chouchane, A.; Ben Mansour, S.; Slama, Y.; Hafsia, M.; Maoua, M.; Mrizak, N.; Naija, W.
Abstract : Introduction: The shortage of doctors has become a worrying problem in Tunisia. It is influenced by the phenomenon of immigration which remains poorly studied despite its magnitude. Objectives: To describe the migration intentions of Tunisian young doctors and to identify the associated factors that influence their decisions. Methods: This is a cross-sectional, analytical survey conducted between January and June 2019. It included all young doctors practicing in academic hospitals of Sousse (Tunisia). Data collection was based on a standardized self-administered questionnaire. Results: A total of 182 valid questionnaires were collected. The median age was 26.9±2.5 years and the sex-ratio was 0.47. Immigration projects were reported by 38.5% of participants. The main destination was France (36.3%%). The main contributing factors were marital status (p<10-3), resident status (p=0.002), surgical specialty (p<10-3), personal dissatisfaction (p=0.003), underpayment (p<10-3), workload and difficult work conditions (p<10-3), lack of appropriate training (p<10-3), financial crisis and economic instability (p<10-3), lack of a clear strategy for the healthcare system (p=0.005) and the impression by the model of other doctors who left Tunisia (p=0.01). Conclusions: The rate of migration intentions expressed in this study highlights the emergent need of interventions emanating from the Tunisian health-care system's problems in order to stop the flow of young doctors towards developed countries in quest of better conditions. Disclosure: No significant relationships.